Maternal and neonatal morbidity in relation to the instrument used to assist in mid-cavity rotational operative vaginal delivery: a prospective cohort study. (18th April 2012) - Venne, MV; Bahl, R; MacLeod, M; Strachan, BK; Murphy, DJ
Abstract : Introduction: Various instruments are available to assist a mid-cavity delivery requiring rotation of the fetal head. There is a lack of robust evidence comparing maternal and neonatal morbidity associated with the use of these instruments. Objective: To compare the maternal and neonatal morbidity associated with instrument use to assist a mid-cavity rotational delivery. Study design: A prospective cohort study of 1360 nulliparous women had operative vaginal births in two university teaching hospitals in Scotland and England. Results: In this cohort, 381 women underwent a mid-cavity rotational delivery. One hundred and sixty three women underwent manual rotation followed by non-rotational forceps delivery, , 73 with the assistance of rotational vacuum and 145 with the assistance of rotational forceps. Women who underwent manual rotation and non-rotational forceps delivery were less likely to need moderate or strong analgesia compared to those delivered using rotational forceps (OR 0.56; 95% CI 0.28 - 0.98) but had a greater analgesia use than women delivered using rotational vacuum (OR 2.38; CI 1.23 - 4.59). Pelvic floor and neonatal morbidity was comparable with either instrument. Compared to manual rotational and non-rotational forceps use, sequential use of instruments was more likely with rotational vacuum use (OR 0.01; 95% CI 0.01- 0.09) and rotational forceps use (OR 0.07; 95% CI 0.01 - 0.63). Conclusions: Mid-cavity instrumental birth has good outcomes overall and the morbidity with Kiellands forceps is comparable to vacuum and manual rotation. Forceps deliveries have a greater analgesia usage whereas vacuum deliveries result in more sequential use of instruments.